CHARACTERISTICS VARIATION OF BLUE SWIMMING CRAB FISHERIES IN CIREBON REGENCY, WEST JAVA AND DEMAK REGENCY, CENTRAL JAVA - Pulung, Karto; Taurusman, Am Azbas; Wiryawan, Budy (Jurnal Penelitian Perikanan Laut (Albacore), 2025)
Blue Swimming Crab (BSC) is an Indonesian fishery export commodity that has high economic value, with the largest BSC production in Indonesia in WPPNRI 712. Cirebon and Demak are the centers of BSC landing base in WPPNRI 712. Data and information on fishery characteristics are needed as a basis for arranging sustainable fishery management policies. This study aims to analyze variations in BSC fishery characteristics in the Cirebon and Demak districts. This study was conducted from August to September 2024 in both locations. Data collection was carried out using field observation and interview methods, and samples were taken using a purposive sampling method. The data analysis was carried out by comparing fisheries characteristics of two locations and evaluating compliance with applicable laws and regulations. The results of the study showed that there were variations in the characteristics of BSC fisheries in Cirebon and Demak, namely: boat, fishing gear, fishing grounds, catch composition, and socio-economic conditions of BSC fisheries. Fishers used traps, bottom gillnet, bottom otter boat trawl, and dregde (specifically in Cirebon) to catch BSC with boats 1-2 GT size. Traps and bottom gillnets are allowed fishing gear operating in Indonesian waters, while bottom otter boat trawl and dredge, as non-permitted gears, have a detrimental impact on fish resources and its environment. The BSC is the main target of traps and bottom gillnets, while these are as bycatch for bottom otter boat trawl and dredge. Demak fishers sell fresh BSC, while in Cirebon, they sell BSC meat and fresh. Key words: blue swimming crab, Cirebon, Demak, fisheries characteristics, WPPNRI 712